2014
DOI: 10.1007/s11284-014-1194-6
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil heterotrophic respiration, carbon availability, and microbial function in seven forests along a climate gradient

Abstract: Soil microbial communities play an essential role in soil carbon (C) emission and C sequestration in forest ecosystems. However, little information is available regarding the relationship between soil C dynamics and microbial substrate utilization at large scales. Along the North-South Transect of Eastern China (NSTEC), seven forests representative of boreal, temperate and tropical biomes were examined. Soil heterotrophic respiration (R h ), soil dissolved organic C (DOC), microbial biomass C (MBC), and microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 58 publications
4
21
0
Order By: Relevance
“…Therefore, increased availability of either soil carbon or nitrogen is expected to stimulate microbial growth and activity in soils4546, leading to the subsequent changes in Q 10 of R S and R H 47. In this study, we found that TOC and MBC were key factors affecting the temperature sensitivities of both daytime R S and R H and nighttime R S and R H during DS (Figs 4 and 5).…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, increased availability of either soil carbon or nitrogen is expected to stimulate microbial growth and activity in soils4546, leading to the subsequent changes in Q 10 of R S and R H 47. In this study, we found that TOC and MBC were key factors affecting the temperature sensitivities of both daytime R S and R H and nighttime R S and R H during DS (Figs 4 and 5).…”
Section: Discussionmentioning
confidence: 55%
“…The C flux through soil respiration (SR) is a vital component of the global C cycle; it represents approximately 10% of the atmospheric C pool, and is 10 times greater than that from fossil fuel combustion [3]. Consequently, even slight changes in understory plant community composition and traits could affect SR through shifts in productivity [4], changing litter inputs and altering the soil microclimate [5,6]. Many studies have reported that plants can control the balance between plant C inputs and losses [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Root respiration (and associated mycorrhizal fungi) and microbial respiration constitute soil-atmospheric exchange of CO 2 , they are the most important C efflux in the ecosystem, and both of them are regulated by soil N availability (Fang et al , 2014a. However, the effects of increased N deposition on soil CO 2 flux are high variable, including promotion (Cleveland and Townsend 2006;Contosta et al 2011), inhibition (Mo et al 2008;Janssens et al 2010), and no change (Allison et al 2008), depending on the level and the form of N addition (Fang et al 2012), on the duration of N addition (Hasselquist and Högberg 2014), and on distinct stages of N saturation (Sutton et al 2011).…”
Section: Introductionmentioning
confidence: 99%